Comparative effectiveness of primary radiotherapy versus surgery in elderly patients with locally advanced oropharyngeal squamous cell carcinoma. (January 2019) - Sher, David J.; Yan, Jingsheng; Day, Andrew; Sumer, Baran D.; Pham, Nhat-Long; Khan, Saad; Zhu, Hong
Highlights: There were no differences in survival between surgery and CRT. Primary CRT increased gastrostomy dependence but not osteonecrosis or stricture. Chemotherapy improved survival in the definitive but not postoperative RT setting. Only cisplatin- and taxane-based regimens improved survival. Abstract: Objectives: To determine the comparative effectiveness of primary radiotherapy (RT) and primary surgery (PS) for locally advanced oropharyngeal squamous cell carcinoma (OPSCC). Materials and methods: Eligible individuals were patients in the SEER-Medicare registry diagnosed with locally advanced OPSCC between 2000 and 2011. Patients were categorized as receiving either primary RT ± chemotherapy, or PS ± adjuvant RT or chemoradiotherapy (CRT). Overall survival (OS) was analyzed using Cox multivariable analysis (MVA). Risks of gastrostomy dependence (GD), esophageal stricture (ES), and osteoradionecrosis (ORN) were analyzed using logistic regression. Results: A total of 2754 patients (69% RT, 31% PS) were included in this cohort, with a median age of 72 years. Patients treated with RT, CRT and PS experienced 3-year OS outcomes of 36.1%, 52.8%, and 54.9%, respectively (p < 0.001). Increasing age, unmarried status, increasing comorbidity, lower income, base of tongue (BOT) site, higher stage, no prior PET, and RT alone (but not CRT) were associated with inferior OS. Independent predictors of GD at 6 months included black race, BOT site, advanced stage, and CRT. The risks of ORN and stricture were not associated with treatment modality. Concurrent chemotherapy improved OS with definitive RT but had no impact in adjuvant RT. Only cisplatin- and taxane-containing regimens improved OS, but all concurrent agents, including cetuximab, significantly worsened GD. Conclusion: Local therapy decisions for locally advanced OPSCC must be individualized, with CRT increasing acute and chronic GD. The differential survival impact of concurrent chemotherapy in the definitive and adjuvant setting may be a consideration in decision-making.